Intervensi Terapi Audio dengan Murottal Surah Ar-Rahman terhadap Perilaku Anak Autis - Mayrani, Eva Dwi; Hartati, Elis (Jurusan Keperawatan FIKES UNSOED, 2013)
Behavioral disturbances which usual happen on children with autism are social interaction, communication, motor behavior, and emotion disturbances. This research aims to identify and describe the influences of audio therapy with surah Ar-Rahman murrotal in children with autism. The numbers of sample in this study were 18 children selected by purposive sampling method based on inclusion and exclusion criteria. Instrument which used to measure pretest and posttest was checklist of behavioral in children with autism. The average of pretest and posttest value were 5.06 and 4.06 and total of respondent with behavioral disturbance decreased after got the therapy. The results showed that audio therapy with surah Ar-Rahman murottal decreased behavioral disturbances of the children with autism in social interaction, motor behavior, and emotion aspects. The study can be a reference and consideration for parents and Special Schools to implement the audio therapy with surah Ar-Rahman murottal as a companion therapy that is cheap and does not cause side effects.